Retroactive correction for white-light dispersion as an edge-detection problem in ultrafast spectroscopies - Kefer, Oskar; Buckup, Tiago; Kolesnichenko, Pavel V. (Applied optics, 2024)
Broadband pump-probe spectroscopy is one of the most popular implementations of femtosecond time-resolved spectroscopy, due to its well-established routines of construction, operation, and data post-processing. Compensation for dispersion of broadband probe pulses covering both near-UV and visible spectral range is not trivial. In such cases, retroactive numerical correction schemes are widely employed. For example, for samples in solution, this is achieved by a separate measurement of the coherent artifact. However, when a reference sample is unavailable, as is the case for most solid-state materials, retroactive characterization of the broadband probe dispersion using a similar approach can be challenging if not impossible. Here, we overcome this limitation by conceptualizing the onset of pump-probe signal as an edge and apply multi-pass wavelet convolution to broadband pump-probe spectra. This reveals prominent white-light dispersion akin to separate measurements of the coherent artifact, but free from contributions of cross-phase modulation. We demonstrate the high sensitivity of the approach, rendering it robust even to cases with small signal-to-noise ratios. We believe that the approach has great potential to be adopted in various laboratories and related industries as part of an automated dispersion-correction routine.
Gesehen am 18.09.2024